Agriculture, climate change and sustainability: The case of EU-28. (October 2019) - Agovino, Massimiliano; Casaccia, Mariaconcetta; Ciommi, Mariateresa; Ferrara, Maria; Marchesano, Katia
Highlights: An index of Sustainable Agriculture for the EU-28 over the period 2005–2014 is computed. A Granger-causality test for panel data is implemented. A negative bidirectional relationship between climate change and agricultural yields is verified. A negative bidirectional relationship between climate change and sustainable agriculture is identified. Conventional agriculture negatively affects sustainable agriculture. Abstract: Agriculture and climate change are characterized by a complex cause-effect relationship. The agricultural sector generates significant quantities of gas emissions that affect climate. The rise in the concentration of greenhouse gases in the atmosphere, the increase in temperatures as well as changes in the precipitation regime have repercussions on the volume, quality and stability of the agricultural and zoo technical production, but also on the natural environment in which agriculture is practiced. Based on the above, the purpose of the paper is twofold. Firstly, through the Wroclaw Taxonomic Method, we construct a composite indicator, called the Index of Sustainable Agriculture (ISA), and analyse 28 countries that have joined the European Union from 1 July 2013 to today (EU-28) over the period 2005–2014, according to 16 variables. Secondly, the Granger-causality test for panel data is implemented in order to verify the causal relationship among the ISA, climate change and agricultural production. In other words, we test which of the three analyzed variables turns out to be the cause variable and which, instead, turns out to be the effect variable. Furthermore, we test if there is a bidirectional causality among the variables. This analysis provides a wide overview on how European countries rank according to the ISA and its three crucial pillars, i.e. environmental, economic and social. Moreover, important causality relationships among the ISA, climate changes (approximated by mean annual temperature and mean annual precipitation and provided by the Climate Research Unit (CRU) Time-Series (TS) Version 3.22 of the University of East Anglia) and agricultural production (approximated by wheat and spelt yields and provided by EUROSTAT) are identified. In particular, the following hypotheses are verified: 1) there is a negative bidirectional relationship between climate change and agricultural yields; 2) there is a negative bidirectional causal relationship between climate change and sustainable agriculture; 3) conventional agriculture negatively affects sustainable agriculture.